Coronary Thrombosis without Dissection following Blunt Trauma - Archana Sinha; Michael Sibel; Peter Thomas; Francis Burt; James Cipolla; Peter Puleo; Keith Baker (Case Reports in Cardiology)
Blunt trauma to the chest resulting in coronary thrombosis and ST elevation myocardial infarction (STEMI) is a rare but well-described occurrence in adults. Angiography in such cases has generally disclosed complete epicardial coronary occlusion with thrombus, indistinguishable from the findings commonly found in spontaneous plaque rupture due to atherosclerotic disease. In all previously reported cases in which coronary interrogation with intravascular ultrasound (IVUS) was performed in association with acute revascularization, coronary artery dissection was implicated as the etiology of coronary thrombosis. We present the first case report of blunt trauma-associated coronary thrombosis without underlying atherosclerosis or coronary dissection, as documented by IVUS imaging.